2010
DOI: 10.1098/rspb.2010.1678
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the stress-linked immunocompetence handicap hypothesis in human male faces

Abstract: The stress-linked immunocompetence handicap hypothesis (SL-ICHH) of sexual selection incorporates a role of the stress hormone corticosterone (C; cortisol in humans) in relationships between testosterone (T), immunity and secondary sexual trait expression. In support of this, C has been shown to mediate and moderate relationships between T and immune response and to be inversely related to attractiveness in some avian species. We predicted that female preferences for cues to T in human male faces would be cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 49 publications
(71 reference statements)
8
36
4
Order By: Relevance
“…Once again, women preferred the faces of males with low cortisol, and didn't express preferences for testosterone. In this second study, we also tested the effects of the hormones on perceived dominance and health, finding that low cortisol faces were also rated as more dominant and healthy than high cortisol faces [26,27]. The findings of both studies are consistent with work in other species that shows that females prefer males with low levels of glucocorticoids.…”
Section: How Do Glucocorticoids Influence Mate Choice?supporting
confidence: 76%
See 3 more Smart Citations
“…Once again, women preferred the faces of males with low cortisol, and didn't express preferences for testosterone. In this second study, we also tested the effects of the hormones on perceived dominance and health, finding that low cortisol faces were also rated as more dominant and healthy than high cortisol faces [26,27]. The findings of both studies are consistent with work in other species that shows that females prefer males with low levels of glucocorticoids.…”
Section: How Do Glucocorticoids Influence Mate Choice?supporting
confidence: 76%
“…We concluded that women can detect cues to cortisol in the male face, and that low cortisol is desirable in a male partner. We also suggested that low cortisol may be associated with beneficial heritable characteristics as women expressed the strongest preferences for facial cues to low cortisol at times when they were most likely to conceive [26]. We replicated this pattern of results in a different sample of faces with a novel sample of female raters, again recruited from UK student populations.…”
Section: How Do Glucocorticoids Influence Mate Choice?supporting
confidence: 57%
See 2 more Smart Citations
“…Steroid hormones may provide a link between F 0 and condition. Growing evidence indicates that glucocorticoids such as the stress hormone cortisol negatively interact with testosterone in predicting immune function and influencing the expression of secondary sex traits [25][26][27]. Infection stimulates cortisol production [28], which downregulates androgen receptors and inhibits the action of testosterone on target tissues [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%